(untitled) (Profetik: Jurnal Komunikasi, 2021)
In academic research, the Internet and the public domain’s topic now has a permanent place; it is entering the mainstream of political communication studies. The coming out of the same ideas and opinions with social media can build a discourse for further discussion. One of the viral and trending discourses on Indonesian twitter was the rejection of OMNIBUSLAW; many people issued opinions using the hashtags #MosiTidakPercaya and #Tolakomnibuslaw, which emerged as a result of the passing of the omnibus law, which contains many irregularities in its ratification. This research was conducted by taking data on Twitter in October 2020 and processed using the Nvivo 12 Plus software. The results of this study indicate that the social media using twitter as information is 25%, where the public uses Twitter as a means of seeking information on the Job Creation Bill in its development process and its rejection in it, political communication is 48%, communication that is built has an interest in running political goals and as a movement. 25% of politics in pressuring the government and forming public opinion on the Work Creation Bill and a place for public space to communicate can be seen in the public space that people are interested in voicing their anxieties if there is a disagreement of opinion between stakeholders and the wider community.